Stakeholder collaboration model for enhancing English communication competencies in early childhood teacher education programs - Pusari, Ratna Wahyu; Fakhruddin, Fakhruddin; Suharini, Erni; Yulianto, Arief (Edelweiss Applied Science and Technology, 2025)
The need for English communication skills is increasing in bilingual early childhood education institutions, but there is no effective collaboration model to prepare competent graduates from early childhood education study programs. The objective of this study is to develop a role model for stakeholders to improve graduates’ English communication skills. This research and development (R&D) study is based on the Borg and Gall model and involved 85 teachers, 24 school principals, and 14 PAUD program students. Data were collected through questionnaires, interviews, and focus group discussions (FGDs). Preliminary results of the study show that 98% of PAUD institutions have introduced English, but only 28% require teachers to have the appropriate skills. The developed internal-external collaboration model integrates learning strategies and field practices. Its effectiveness is demonstrated by a t-value (7.728) higher than the critical t-value (1.697), as well as by expert validation, which shows that 77% of respondents rated this model as “very good.” This model has proven to be very effective in improving graduates’ English communication skills, bridging the gap between field requirements and graduate competencies through systematic collaboration between higher education institutions and PAUD institutions.